2011
DOI: 10.1371/journal.ppat.1002319
|View full text |Cite
|
Sign up to set email alerts
|

Toll-8/Tollo Negatively Regulates Antimicrobial Response in the Drosophila Respiratory Epithelium

Abstract: Barrier epithelia that are persistently exposed to microbes have evolved potent immune tools to eliminate such pathogens. If mechanisms that control Drosophila systemic responses are well-characterized, the epithelial immune responses remain poorly understood. Here, we performed a genetic dissection of the cascades activated during the immune response of the Drosophila airway epithelium i.e. trachea. We present evidence that bacteria induced-antimicrobial peptide (AMP) production in the trachea is controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 64 publications
2
60
0
Order By: Relevance
“…However, the limited duration of axon protection afforded by DLK ablation argues against its centrality in an axon degeneration pathway. Indeed, we and others have identified additional molecules whose loss or inhibition delays injury-induced axon degeneration (Barrientos et al, 2011;Gerdts et al, 2011;Wakatsuki et al, 2011;Bhattacharya et al, 2012;Babetto et al, 2013).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the limited duration of axon protection afforded by DLK ablation argues against its centrality in an axon degeneration pathway. Indeed, we and others have identified additional molecules whose loss or inhibition delays injury-induced axon degeneration (Barrientos et al, 2011;Gerdts et al, 2011;Wakatsuki et al, 2011;Bhattacharya et al, 2012;Babetto et al, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…The TIR adaptor proteins have been well studied as dynamic scaffold molecules promoting the downstream signaling of Toll-like receptors and have important roles in innate immunity (O'Neill and Bowie, 2007). SARM is unique among these proteins in that it has been reported to act as a negative regulator of innate immunity signaling (Carty et al, 2006;Akhouayri et al, 2011). Unlike the other TIR adaptors, SARM is preferentially expressed in the nervous system (Kim et al, 2007) and is linked to neural cell fate specification (Chuang and Bargmann, 2005), dendritic arborization (Chen et al, 2011), and microglial activation (Szretter et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the sizes of the families of Toll receptors in Drosophila and mammals are similar, with about 10 members, phylogenetic analysis has clearly indicated that Toll receptors evolved independently in different animal phyla (48,49). In Drosophila, only Toll itself has so far been shown to participate in the induction of an immune response in flies, although Toll-8 acts as a negative regulator of antimicrobial defenses in the respiratory tract (50)(51)(52)(53). Drosophila Toll receptors are highly expressed during embryogenesis, pointing to developmental functions (49,54).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Toll-like receptor 4 (TLR4) can bind lipopolysaccharide on the surface of bacteria (36), whereas TLR3 recognizes double-stranded RNA, leading to the activation of the NF-B pathway (37). Drosophila Toll7 recognizes viruses and activates antiviral autophagy (38), Drosophila Toll8 negatively regulates the antimicrobial response (39), and Drosophila Toll1 regulates the systemic immune response (40). This study showed that Toll1, Toll4, Toll6, and Toll7 play important roles in antiviral immunity in shrimp.…”
Section: Discussionmentioning
confidence: 99%